2015
DOI: 10.1093/cid/civ198
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Outbreak of Mycobacterium chimaera Infection After Open-Chest Heart Surgery

Abstract: The epidemiological and microbiological features of this prolonged outbreak provided evidence for the airborne transmission of M. chimaera from contaminated heater-cooler unit water tanks to patients during open-heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
298
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(331 citation statements)
references
References 29 publications
9
298
0
15
Order By: Relevance
“…Cases have been reported worldwide reflecting the global problem of microbial colonisation and the need for effective management of HCUs [1][2][3][4] . This review summaries the knowledge to date as well as the challenges faced by those who have to prevent and control infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cases have been reported worldwide reflecting the global problem of microbial colonisation and the need for effective management of HCUs [1][2][3][4] . This review summaries the knowledge to date as well as the challenges faced by those who have to prevent and control infection.…”
Section: Introductionmentioning
confidence: 99%
“…Reported contamination rates of HSC grafts range from 1% to 45%. [3][4][5] The clinical significance of infusion of contaminated HSC products is unclear. When fresh products are used, contamination is often not identified prior to HSC infusion.…”
Section: Staphylococcus Aureus Bloodstream Infection Due To Contaminamentioning
confidence: 99%
“…Of 26 patients who received grafts contaminated with highly pathogenic bacteria (eg, S. aureus), none developed symptoms or had a positive culture matching an organism found in the HSC graft. 3 In prior reports of infections putatively caused by graft contamination, confirmation that the graft was the source of infection was based solely on the finding of identical species. 6,7 Contrary to these prior reports, we present a case of catheter-related bloodstream infection with methicillinsusceptible S. aureus due to a contaminated HSC graft in which pulsed-field gel electrophoresis (PFGE) confirmed that the graft and patient isolates were identical.…”
Section: Staphylococcus Aureus Bloodstream Infection Due To Contaminamentioning
confidence: 99%
See 2 more Smart Citations